PENGARUH FINANCING TO DEPOSIT RATIO (FDR), DANA PIHAK KETIGA (DPK) DAN RETURN ON ASSET (ROA) TERHADAP PEMBIAYAAN MUSYARAKAH - Djoko Sigit Gunanto; Suprihati Suprihati; Firma Windi Aristi (ITB AAS INDONESIA Surakarta, 2018)
This study aims to determine the effect of Financing To Deposit Ratio (FDR), Third Party Funds (TPF) and Return on Assets (ROA) on musyarakah financing on Bank Syariah Mandiri from 2010-2017 both partially and simultaneously. This study uses quantitative data types. The data used uses secondary data obtained from quarterly financial reports. The method used in this study is to use the classic assumption test method where the Classic Assumption test consists of four tests namely Normality test, Multicollinearity test, Heterocedasticity test and Autocorrelation test in addition to using the Classical Assumption test, in this study also uses the test with data analysis from the analysis Multiple linear regression and using t test or partial test and F test or test simultaneously or together. The population in this study is Islamic banking, namely Bank Syariah Mandiri in 2010-2017 as many as 32 taken by purposive sampling. The results showed that the variables that affect Musyarakah financing are variables Financing To Deposit Ratio (FDR) with a P-value of 0,000 where this value is greater than 0.05 and the value of t count is -4.916 where this value is greater than the value of t table namely 2,0484 and Third Party Funds with a P-value of 0,000 where this value is greater than 0.05 and the value of t count is 4,559 is greater than the ttable value of 2,0484 while the variable that has no effect on musyarakah financing is the Return on Asset variable (ROA) with a P-value of 0.428 where this value is greater than 0.05 and tcount is smaller than t table where the value of t count is 0.805 and the value of t table is 2.0484. Simultaneously all variables namely FDR, DPK and ROA jointly influence Musyarakah financing on Bank Syariah Mandiri (BSM) in 2010-2017 with a significance value of 0,000 where the sig value is smaller than 0.05 while the Fcount value is greater than Ftable value where Fcount value is 25,160 while Ftable value is 2,95. Keywords: Financing To Deposit Ratio (FDR), Third Party Funds (DPK), Return on Assets (ROA), musyarakah